Perlindungan Hukum Terhadap Hak Pekerja Rumah Tangga di Perumahan Villa Sentosa Indah Kota Jambi - Gilbert, Oldie; Rosmidah, Rosmidah (Universitas Jambi, Fakultas Hukum, 2024)
This research aims to determine and analyze legal protection for the rights of Domestic Workers (PRT) and obstacles in implementing legal protection for the rights of domestic workers in the Villa Sentosa Indah Housing Complex, Jambi City. This research uses the Empirical Juridical research type by collecting data directly from respondents through field research to determine the problems that arise in implementing legal protection for the rights of domestic workers in the Villa Sentosa Indah Housing Complex, Jambi City. The results of research conducted by the author, involving 18 domestic worker respondents and 18 user respondents in the Villa Sentosa Indah Housing Complex, Jambi City, show that there are still users who do not comply with wage agreements, do not include domestic workers in the Social Security program, do not give leave rights to domestic workers and do not report the use of domestic workers' services to the Head of the Neighborhood Association. An obstacle in implementing legal protection in the Villa Sentosa Indah Housing Complex, Jambi City is the absence of socialization regarding the Minister of Manpower Regulation regarding the Protection of Domestic Workers. The results of interviews conducted by the author in October 2023 with 18 domestic worker respondents and 18 user respondents in February 2024, stated that they had never received socialization information regarding the Minister of Manpower Regulation on the Protection of Domestic Workers. In fact, the Head of the Neighborhood Association number 31 also said that up to now no information has been received regarding the socialization of the Minister of Manpower Regulation on the Protection of Domestic Workers carried out by the government.